TCF7L2 gene polymorphism in populations of f ive Siberian ethnic groups - L. E. Tabikhanova; L. P. Osipova; T. V. Churkina; E. N. Voronina; M. L. Filipenko (Вавиловский журнал генетики и селекции)
Investigation of the frequencies of functionally signif icant gene variants in the context of medical biology and gene geography is a relevant issue for studying the genetic structure of human populations. The transition from a traditional to an urbanized lifestyle leads to a higher incidence of civilizational diseases associated with metabolic disorders, including type 2 diabetes mellitus. The goal of the present paper is to analyze the frequencies of functionally signif icant gene alleles in the metabolic prof iles of indigenous Siberian peoples to identify the gene pool resilience, evaluate the susceptibility of various ethnic groups to metabolic disorders under changing environmental conditions, and predict the epidemiological situation that may occur in the near future. The study was performed in the monoethnic samples of eastern and western Buryats, Teleuts, Dolgans, and two territorial groups of Yakuts. A real-time PCR was used to determine the frequencies of single nucleotide polymorphisms (SNPs) G103894T, rs12255372, and C53341T, rs7903146 in the TCF7L2 gene. The results obtained were compared to the frequencies identif ied for Russians from Eastern Siberia and the values available in the literature. The frequencies of the polymorphic variants studied in the samples from the indigenous Siberian peoples place them in between Caucasian and East Asian populations, following the geographic gradient of polymorphism distribution. A signif icantly lower occurrence of type 2 diabetes risk alleles TCF7L2 (103894T) and TCF7L2 (53341T) in the samples of indigenous Siberian peoples compared to Russians was observed, which agrees with their lower susceptibility to metabolic disorders compared to the newcomer Caucasian population. Taking into account urbanization, a reduced growth in type 2 diabetes incidence may be predicted in indigenous Siberian peoples, i. e. Buryats, Yakuts, Dolgans, and Teleuts, compared to the newcomer Caucasian population. A further study of population structure with respect to different metabolic prof ile genes is required to better understand the molecular genetic foundations of the adaptive potential of indigenous Siberian peoples.